Acute effects of three resistance exercise programs on energy metabolism - Nitzsche, N.; Baumgärtel, L.; Weigert, M.; Neuendorf, T.; Fröhlich, M.; Schulz, H. (International Journal of Sports Science, 2017)
The knowledge about metabolic effects of different training programs is of huge importance for the regulation of resistance training. Most studies investigated the effect of the variation of a single load character on physiological parameters such as blood lactate and oxygen intake. Therefore, the present study investigates the physiological reactions on practice-oriented resistance exercise programs with different loads and training volumes. 24 male subjects (25.6 ± 5.9 years, 171 ± 4 cm, 74.3 ± 5.3 kg) were randomly assigned into three different resistance training groups (G1 = 30/30/3/60, G2 = 50/20/3/90, G3 = 70/10/4/90; respectively % of one repetition maximum /repetitions /number of sets /rest between sets). Exercises squats, bench press, biceps curl, french press, and rowing were completed in a randomized order. Heart rate (HR), breathing frequency (BF), oxygen uptake (relVO2) and blood lactate (La) were measured at the end of each set. Mean value of all sets in each exercise was used for statistical analysis (ANOVA). Performance was calculated using the relative power index (RPI). There were significant differences in the RPI (ANOVA p between G2 and G3 (ANOVA p0.05). The (relVO2) and HR showed significant differences between the exercises (ANOVA p relVO2 but not in La were shown between the exercises. In summary, the present study shows, that the physiological effects of the three different strength training programs on VO2, HR, La and BF differs very little, despite the strongly differing RPI. The selection of the exercise seems to be especially important for the acute adaptations of VO2 and HR, but not for lactate accumulation.